Автоматизированное формирование расчетных моделей турбогенераторов для программной среды FEMM - Милых, В.И.; Полякова, Н.В. (Електротехніка і електромеханіка, 2015)
Представлены принципы автоматизированного формирования графической и физической моделей турбогенераторов
на алгоритмическом языке Lua для расчета их магнитных полей и параметров в программной среде пакета FEMM.
Возможности составленного скрипта Lua демонстрируются на примере реального турбогенератора. Представлені принципи автоматизованого формування графічної і фізичної моделей турбогенераторів на
алгоритмичній мові Lua для розрахунку їх магнітних полів і параметрів у програмному середовищі пакету FEMM.
Можливості складеного скрипту Lua демонструються на прикладі реального турбогенератора. Attention is paid to the popular FEMM (Finite Element Method
Magnetics) program which is effective in the numerical calculations of the magnetic fields of electrical machines. The main problem of its using - high costs in time on the formation of a graphical
model representing the design and on the formation of the physical
model representing the materials properties and the winding currents of machines – is solved. For this purpose, principles of the
automated formation of such models are developed and presented
on the turbogenerator example. The task is performed by a program written in an algorithmic language Lua integrated into the
package FEMM. The program is universal in terms of varying the
geometry and dimensions of the designed turbogenerators. It uses a
minimum of input information in a digital form representing the
design of the whole turbogenerator and its fragments. A general
structure of the Lua script is provided, significant parts of its text,
the graphic results of work's phases, as well as explanations of the
program and instructions for its use are given. Performance capabilities of the compiled Lua script are shown on the example of the
real 340 MW turbogenerator.